Clinical implications of lung neuroendocrine neoplasm classification. Issue 4 (3rd April 2021) - Metovic, Jasna; Barella, Marco; Harari, Sergio; Pattini, Linda; Albini, Adriana; Sonzogni, Angelica; Veronesi, Giulia; Papotti, Mauro; Pelosi, Giuseppe
ABSTRACT: Introduction: Neuroendocrine neoplasms of the lung (Lung NENs) encompass NE tumors (NETs), which are in turn split into typical and atypical carcinoids, and NE carcinomas (NECs), which group together small-cell carcinoma and large-cell NE carcinoma. This classification is the current basis for orienting the daily practice of these patients, with diagnostic, prognostic, and predictive inferences. Areas covered: The clinical implications of lung NEN classification are addressed according to three converging perspectives, which were dissected through an extensive literature overview: (1) how to put intratumor heterogeneity into the context of the current classification; (2) how to contextualize immunohistochemistry markers to improve diagnosis, prognosis, and therapy prediction; and (3) how to use immuno-oncology strategies for life-threatening NECs, which still account for 90% or more of lung NENs. Expert opinion: We provide practical insights to account for intratumor heterogeneity, practice the choice of immunohistochemistry markers, and emphasize once again the added value of immuno-oncology in the setting of personalized medicine of lung NENs.